2015
DOI: 10.1111/inr.12223
|View full text |Cite
|
Sign up to set email alerts
|

Does antenatal education reduce fear of childbirth?

Abstract: A systematic antenatal education programme, as part of routine antenatal care services, would help reduce the rate of interventional labour and facilitate pregnant women's conscious participation in the act of labour by reducing their fear of childbirth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
85
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 22 publications
(26 reference statements)
3
85
2
7
Order By: Relevance
“…(), and in many other national and international studies, pregnant women were found to experience moderate levels of FOC as measured by WDEQ‐A (Karabulut et al. ; Toohill et al. ).…”
Section: Discussionmentioning
confidence: 87%
“…(), and in many other national and international studies, pregnant women were found to experience moderate levels of FOC as measured by WDEQ‐A (Karabulut et al. ; Toohill et al. ).…”
Section: Discussionmentioning
confidence: 87%
“…This requires the creation of a strong and positive relationship between pregnant women and healthcare professionals by means of effective communication, full acceptance, empathy, support, appreciation, and respect (Sydsjö et al, 2015). The positive effect of psychoprophylaxis on reducing FOC among women has also been demonstrated in other studies (Karabulut et al, 2016;Kızılırmak, Başer, 2016;Serçekuş, Başkale, 2016).…”
Section: Discussionmentioning
confidence: 89%
“…In other experimental studies on the same topic, women who attended pregnant education classes were found to have less fear of childbirth. 4,6,10 In Finland study reported that pregnant women in antenatal education group had less fear of childbirth than those in the control group. 9 Fabian and colleagues reported that the majority of women (74%) found antenatal education classes helpful in preparing for childbirth and early parenthood.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Koehn reported that childbirth education less infant mortality, less discomfort and less disability. 7 Previous studies have shown that benefits these classes reduced fear of childbirth, helpful in preparing for childbirth and early parenthood, higher likelihood breastfeeding, increased birth satisfaction, decreased need for analgesic medication.…”
Section: Pregnant Education Classesmentioning
confidence: 99%
See 1 more Smart Citation